The Processing Design of Jute Spun Yarn/PLA Braided Composite by Pultrusion Molding - Anin Memon (Advances in Mechanical Engineering, 2013)
Prevalently, the light has been shed on the green composite from the viewpoint of environmental protection. Jute fibers are natural fibers superior due to light weight, low cost, and being environmentally friendly corresponding to the green composite materials. Meticulously, fibers of polylactic acid (PLA) thermoplastic biopolymer were used as the resin fibers. In this study, the fabrication of tubular jute spun yarn/PLA braided composite by pultrusion molding was presented. The intermediate materials were prepared by commingled technique. The braiding technique manufactured preform which had jute fiber diagonally oriented at certain angles with the glass fiber inserted into the braiding yarns along the longitudinal direction. The braided preforms were pulled through a heated die where the consolidation flow took place due to reduced matrix viscosity and pressure. The pultrusion experiments were done with jute/PLA commingled yarns and combined with glass fiber yarns to fabricate the tubular composite. Impregnation quality was evaluated by microscope observation of the pultruded cross-sections. The flexural mechanical properties of the pultruded were measured by four-point bending test.